Research of the model of a respondent in the system of automation of estimating quality of activity of teachers - Дударь, Зоя Владимировна; Вечур, Александр Владимирович; Сорока, Олег Александрович (Eastern-European Journal of Enterprise Technologies, 2011)
The general characteristic of the model of a respondent is given. Results of analysis of the data about interaction of a respondent with elements of the questioning system are stated. Possible variants of improving the structure of elements of questioning system are described